Glyphochaitophorus, a new genus of Chaitophorini (Hemiptera: Aphididae: Chaitophorinae) from China - Chen, Jing; Li, Zhaoxu; Jiang, Liyun; Qiao, Gexia (Zootaxa, 2021)
Glyphochaitophorus Qiao gen. nov. with one new species Glyphochaitophorus cristaphis Qiao sp. nov. on Acer palmatum from Tibet, China is described and illustrated in the aphid tribe Chaitophorini. A key to Glyphochaitophorus and allied genera is provided.